2020
DOI: 10.1002/andp.201900546
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Imaging Effect Based on Airy Beams with Quadratic Phase Modulation

Abstract: The self‐imaging effect based on Airy beams with quadratic phase modulation (QPM) in 1 + 1 and 2 + 1 dimensions is studied both numerically and analytically. It is demonstrated that, in spite of spatial spectral shape being kept invariant, both the intensity pattern and the accelerating trajectory of this self‐imaging effect depend considerably on the QPM. When the QPM parameter is negative, the self‐imaging accelerating wave exhibits deceleration and then acceleration, and the self‐imaging scope can be expand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…It is shown that by controlling the ballistic trajectories of the multi-Airy beams, [14,15] the auto-focusing effect during propagation of the beams can be easily realized. [26] On the other hand, multi-Airy beams with controllable ballistic trajectories have been applied to produce the self-imaging effect [27] in linear media and the propagation of optical solitons [28] in nonlinear media based on imposing appropriate quadratic and linear phase modulations (QPM and LPM). Noteworthily, the previous work about the propagation of multi-Airy beams with QPM and LPM in which free space or media with different index potential shows interesting results, the auto-focusing effect strongly depends on the phase modulation parameters, and varied interesting propagation trajectories of the beams can be obtained by modulating the phase parameters.…”
Section: Doi: 101002/andp202100165mentioning
confidence: 99%
“…It is shown that by controlling the ballistic trajectories of the multi-Airy beams, [14,15] the auto-focusing effect during propagation of the beams can be easily realized. [26] On the other hand, multi-Airy beams with controllable ballistic trajectories have been applied to produce the self-imaging effect [27] in linear media and the propagation of optical solitons [28] in nonlinear media based on imposing appropriate quadratic and linear phase modulations (QPM and LPM). Noteworthily, the previous work about the propagation of multi-Airy beams with QPM and LPM in which free space or media with different index potential shows interesting results, the auto-focusing effect strongly depends on the phase modulation parameters, and varied interesting propagation trajectories of the beams can be obtained by modulating the phase parameters.…”
Section: Doi: 101002/andp202100165mentioning
confidence: 99%
“…As soon as Airy beams have been introduced into optics with finite energy by Siviloglou in 2007 theoretically [1,2] and experimentally, [3] Airy beams attract a lot of interest because of their innovative properties like self-acceleration, [4][5][6][7][8] selfhealing, [9][10][11][12] autofocusing, [13][14][15] self-focusing in material, [16] and self-imaging based on Airy-Talbot effect. [17,18] Based on these properties, abundant applications have been developed as mentioned in the following. The self-acceleration Airy beams have been used to achieve parabola-like and S-shape electrical discharges, and these electrical discharges can be used for machining and assisting the milling process.…”
Section: Introductionmentioning
confidence: 99%
“…Airy beams have attracted much research interest since their particular properties, they are not only non-diffraction, self-healing but also self-bending [6][7][8][9]. At present, some potential applications based on the unique properties of Airy beams have been explored, such as optical micro-manipulation [10,11], vacuum electron acceleration [12,13], microscopy [14,15] and self-imaging effect [16,17]. Moreover, the propagation dynamics of Airy beams in nonlinear media were also investigated [18].…”
Section: Introductionmentioning
confidence: 99%